Interim Report on Drug Utilization Review of Community Acquired, Nursing Home Acquired and Nosocomial Pneumonia: Clinical, Bacteriological and Radiological Spectrum - CW Chow; N Senathiragah; M Rawji; M Chan; LR Lee-Pack; CK Chan (Canadian Journal of Infectious Diseases)
OBJECTIVES: To review the epidemiology of community acquired, nursing home acquired and nosocomial pneumonia in terms of clinical. bacteriological and radiological features and to examine the spectrum of and response to antimicrobial agents used in its management.